Notes on the larval morphology of Pteromalidae (Hymenoptera: Chalcidoidea) species parasitoids of gall wasps (Hymenoptera: Cynipidae) in Europe - Gómez, Jose F.; Nieves-Aldrey, Jose Luis (Zootaxa, 2012)
A comparative study of the larval morphology and biology of Arthrolytus glandium Bouček, Cecidostiba fungosa Geof-froy in Fourcroy, Cecidostiba geganius (Walker), Pteromalus bedeguaris (Thomson), Pteromalus hieracii (Thomson),Pteromalus isarchus Walker, Rivasia fumariae Askew & Nieves-Aldrey and Stinoplus lapsanae Graham (Pteromalidae)is presented. These eight species are all parasitoids of gall wasps in Europe and are components of communities associatedwith different gall-wasp food guilds: galls on herbs, shrubs and oaks. Special attention was paid to larval body shape, headcapsule characters, the mouthparts and especially the mandibles and the chaetotaxy of the head. Diagnostic characters ofthe genera are provided and except for R. fumariae the terminal instar larvae of all studied species are described and illus-trated for the first time with scanning electron photomicrographs. Information on the biology of each species, including new rearing records, is given.